Multi‐Source Forecast of Solar Cycle Flare Activity Using the Novel Informer‐Based Models - Jie Cao; Tingting Xu; Linhua Deng; Miao Wan; Xinhua Zhao; Yang Peng; Xueliang Zhou; Wenhua Wang; Lidong Huang; Wencheng Wang; Lei Yang; Weihong Zhou (Space Weather)
Abstract Solar flares, the significant indicators of solar activity, have an impact on Earth's satellites and communication systems. Accurate prediction of solar flare events is crucial for mitigating these effects. In this work, we use multiple data sources, including Geostationary Operational Environmental Satellites soft X‐ray flare flux and the solar flare index, to forecast solar flare activity during Solar Cycle 25 (SC25). Our results show that: (a) The north‐south asymmetry of solar flare activity during SC25 is well revealed, and the southern hemisphere is greater than the northern one. (b) The Gnevyshev peaks of chromospheric flare activity are clearly identified and they are deeper than other atmospheric activity indicators. The different timescales of solar flare responses to the geomagnetic and interplanetary magnetic fields may be the cause of the Gnevyshev peaks. (c) Chromospheric flare activity lags behind photospheric sunspot activity, indicating that changes in sunspot activity precede flare events. (d) The activity level of SC25 is influenced by the modulating effect of the Gleissberg Cycle, as supported by geomagnetic precursor indices. These results offer valuable insights into the temporal and spatial distribution of solar flare activity during SC25.